Novel Mutations in Sandhoff Disease: A Molecular Analysis Among Iranian Cohort of Infantile Patients - T Zaman; K Banihashemi; O Aryani; H Aryan; M Houshmand (Tehran University of Medical Sciences, 2012)
Background: Sandhoff disease is an autosomal recessive disorder caused by β-hexosaminidase deficiency and accumulation of GM2 ganglioside resulting in progressive motor neuron manifestations and death from respiratory failure and infections in infantiles. Pathogenic mutations in HEXB gene were observed which leads to enzyme activity reduction and interruption of normal metabolic cycle of GM2 ganglioside in sandhoff patients.Methods: Six infantile index patients with typical biochemical and clinical picture of the disease were studied at the molecular level. After DNA extraction and amplification, probands and their parents, were evaluated by direct sequencing of amplicons.Results: We identified 7 different mutations among which 4 were novel. The most prevalent finding (50%) among our population was a 16 kb deletion including the promoter and exons 1-5. The other findings included c.1552delG and c.410G>A, c.362 A>G, c.550delT, c.1597C>T, c.1752delTG.Conclusion: We conclude that Cys137Tyr and R533C mutations may be pathogenic because of changing amino acid and locating at the conserved region and also they have not been observed in hundred controls. Besides, four mutations including: Cys137Tyr, c.1552delG, c.1597C>T and c.550delT fulfilled almost criteria for pathogenic mutation.